Análisis de la infraestructura de TI de la Facultad de Administración, Finanzas e Informática de la UTB para el desarrollo de las actividades académicas 2024. - Andrade Palacios, Daniela Andreina (2024)
The general objective of this research study was to analyze the IT infrastructure of the Faculty of Administration, Finance and Informatics of the UTB for the development of academic activities 2024, for which a field research type was used with a descriptive, exploratory approach, with a qualitative and quantitative methodology, for a population of 88 teachers and a head of the systems department of the data center, using a survey with 8 questions and an interview respectively as an instrument for the collection of information. The results of the research were described in three parts, the first one on the surveys to the teachers who have a divided opinion on the need for the inclusion of new methodologies for education where the academic software requires an adaptation to the current educational needs, as a second point on the realization of the SWOT which allowed to establish four strategies in relation to the combination FO, DO, FA, DA, which are specified in table # 9 and finally the interview which let know the needs of the data center, on the improvements required in parameters of Firewall, Software and the process of automatic updating. Concluding that the methodology currently implemented in the educational institution has to do with collaborative strategies, which depends directly and indirectly on technology and that there is a need for the inclusion of a chatbot system that allows quick and timely interaction for problem solving, for reasons of the network and Moodle academic software, in addition to guide novice students in the development of their activities in relation to the exchange of information.